A DNA walker triggered isothermal amplification method based on freezing construction of AuNP probes and its application in ricin detection. Issue 3 (12th January 2023) - Sun, Xuan; Wang, Weiya; Chai, Yanyan; Zheng, Zhou; Wang, Yu; Bi, Jing; Wang, Qian; Hu, Yonggang; Gao, Zhixian
Abstract : A DNA walker triggered exponential amplification method based on freezing construction of AuNP probes is developed to detect ricin, showing a lower detection limit, satisfactory specificity, and excellent stability in practical application. Abstract : DNA molecular machines are widely used in the fields of biosensors and biological detection. Among them, DNA walkers have attracted much attention due to their simple design and controllability. Herein, we attempt to develop a DNA walker triggered exponential amplification method and explore its application. The AuNP probes in the DNA walker are constructed by a freezing technology, instead of the time-consuming and complex synthesis process of the traditional method. Meanwhile, after the "recognition–cleavage–relative motion" cycle of this DNA walker reaction, the exponential amplification reaction is initiated, and leads to the fluorescence recovery of the molecular beacon. Taking ricin as a target, this new method shows a limit of detection of 2.25 pM by selecting aptamers with strong binding affinity, and exhibits a wide detection range, satisfactory specificity, and excellent stability in practical application. Therefore, our method provides a universal sensing platform and has great prospects in the fields of biosensors, food safety detection, and clinical diagnostics.